REVEAL FACTS OF THE INCREASING NUMBER OF ABORTION CASES IN UNITED STATES BASED ON MOTIVATING FACTORS - Susiati Susiati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2019)
This study is a literature review discussing the increasing number of abortion cases in UnitedStates. Since the decision of Roe v. Wade in 1973, and the legalization of abortion in America, more than56 million lives of babies die. This amount is far greater than the number of victims of massacres duringthe world war. This study uses literature analysis study method. Through this method, conceptualreferences, data and information are collected from various literature sources such as scientific journals,books, research reports and other literature documents; then analyzed by qualitative approach. Theresults show that high cases of abortion in the United States are not solely due to legal abortion in thecountry. In principle, abortion is not an option, but the resultant pressure of circumstances that corneredthem on the weight choice. Therefore, It can reveal several other factors that motivated them to haveabortions, such as: sexual violence factors, medical factors, law and policy factors, income level factors,social factors and psychological factors., , , ,